2021
DOI: 10.1302/0301-620x.103b2.bjj-2020-0583.r2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral anticoagulant use on surgical delay and mortality in hip fracture

Abstract: Aims Current guidelines recommend surgery within 48 hours among patients presenting with hip fractures; however, optimal surgical timing for patients on oral anticoagulants (OACs) remains unclear. Individual studies are limited by small sample sizes and heterogeneous outcomes. The aim of this study was to conduct a systematic review and meta-analysis to summarize the effect of pre-injury OACs on time-to-surgery (TTS) and all-cause mortality among older adults with hip fracture treated surgically. Methods We se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…The inhouse mortality rate was 4% but showed a significant increase for patients on anticoagulants (7.7%) consistent with other studies showing increased mortality for anticoagulants [22] Dettoni et al were able to determine two main factors for increased mortality and complications, namely warfarin and a delay in time to surgery in a large cohort of 875 hip fractures [23]. DOACS were evaluated as a risk for higher mortality and delay to surgery also by a large metaanalysis [24]. Protocols for patients with anticoagulants have been established to enable early surgery [25].…”
Section: Discussionsupporting
confidence: 73%
“…The inhouse mortality rate was 4% but showed a significant increase for patients on anticoagulants (7.7%) consistent with other studies showing increased mortality for anticoagulants [22] Dettoni et al were able to determine two main factors for increased mortality and complications, namely warfarin and a delay in time to surgery in a large cohort of 875 hip fractures [23]. DOACS were evaluated as a risk for higher mortality and delay to surgery also by a large metaanalysis [24]. Protocols for patients with anticoagulants have been established to enable early surgery [25].…”
Section: Discussionsupporting
confidence: 73%
“…VKA inhibit hepatic production of the vitamin K dependent coagulation Factors (II, VII, IX, X), protein C and S. The clinical effect is measured by the INR. Previous studies have reported that the use of VKA was associated with a delay in time-to-surgery and higher mortality for patients requiring emergency orthopaedic procedures [1459][1460][1461][1462] . Furthermore, these patients experience increased surgical blood loss and higher risk of red blood cell transfusions 1463 , highlighting the importance reversing the anticoagulation effect prior to emergency surgery.…”
Section: Daniel Caldeira Geno Merlimentioning
confidence: 98%
“…The poorer outcome among men and those with declining mental function has been reported previously, [21][22][23] as has the worse outcome with hypoalbuminia [24][25][26] and usage of anticoagulation medication. 27 Hypoalbuminemia serves as a marker for malnutrition and increased inflammatory state, whereas usage of anticoagulation and antiaggregant medication is a marker for high cardiovascular risk and bleeding risk. Therefore, patients with those risk factors should be identified early and given additional care, such as dedicated expedited surgical protocols and nutritional support, in order to improve surgical outcome.…”
Section: Discussionmentioning
confidence: 99%